Agglomeration economies and entrepreneurship: testing for spatial externalities in the Dutch ICT industry - Frank G. van Oort; Erik Stam (Max Planck Institute for Research into Economic Systems, 2005)
Although there is growing evidence on the role of agglomeration economies in the formation and growth of firms, both the concepts of agglomeration economies and entrepreneurship tend to be ambiguously defined and measured in the literature. In this study, we aim to improve the conceptualisations and measures of agglomeration economies and entrepreneurship. Indicators of agglomeration economies are analysed in clearly defined urban regimes on three spatial scales in the Netherlands – national zoning, labour market connectedness, and urban size. This is done in order to uncover their effect on two entrepreneurial phases in the firm life cycle - new firm formation and the growth of incumbent firms in the relatively new ICT industry in the Netherlands. In comparison with new firm formation, the growth of incumbent firms is not so much related to spatial clustering of the ICT industry and other localized sources of knowledge economies associated with urban density. Instead, knowledge as an input for growth of incumbent firms is associated with more endogenous (firm internal) learning aspects, reflected by a significant correlate with R&D-investments. Also the effect of local ICT firm competition differs between the two types of firms: a positive effect on new firm formation, but a negative effect on incumbent firm growth. In general, agglomeration economies have stronger effects on the formation of ICT firms than on the growth of ICT firms.
Keywords: M13; R12; L25; D21; L86; L63; O18; R30; 330; agglomeration economies; spatial externalities; entrepreneurship; location; urban regimes; ICT industry; Agglomerationseffekt; Wirtschaftswachstum; Innovation; Räumliche Innovationsdiffusion; Technischer Fortschritt; Wissenstransfer; Regionale Konzentration; Wirtschaftsgeographie; Niederlande